Steal Away - Armstrong, Jennifer; Nang Chan Yeema (New York, USA Scholastic Inc., 1993)
Susannah an orphan and Bethlehem a slave are runaways. They decide that there's a better life in the North, but their journey is not easy.
Keywords: Adult Fiction